2017
DOI: 10.1111/jam.13451
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the relative population size of selected ruminal bacteria following an induced episode of acidosis in beef heifers receiving viable and non-viable active dried yeast

Abstract: The study provided valuable insight into the mechanism by which acidosis affects cattle performance. Individual animal variation in ruminal fermentation partly explained the variability in response to yeast supplementation in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…It has been suggested that feeding LY to receiving cattle can minimize the negative effects of adaptation on feed intake by altering ruminal fermentation patterns and improving cattle health (Adams et al, 1981;Finck et al, 2014). Mohammed et al (2017) also reported that ADY supplementation reduced subacute rumen acidosis in beef heifers by reducing the duration of pH < 5.8 (indicative of subacute ruminal acidosis) when compared with control heifers when the cattle were exposed to an acidosis challenge. The overall ADG and feed efficiency were not affected by LY supplementation in the present study.…”
Section: Effect Of Yeast Supplementation On Growth Performance and Camentioning
confidence: 93%
“…It has been suggested that feeding LY to receiving cattle can minimize the negative effects of adaptation on feed intake by altering ruminal fermentation patterns and improving cattle health (Adams et al, 1981;Finck et al, 2014). Mohammed et al (2017) also reported that ADY supplementation reduced subacute rumen acidosis in beef heifers by reducing the duration of pH < 5.8 (indicative of subacute ruminal acidosis) when compared with control heifers when the cattle were exposed to an acidosis challenge. The overall ADG and feed efficiency were not affected by LY supplementation in the present study.…”
Section: Effect Of Yeast Supplementation On Growth Performance and Camentioning
confidence: 93%
“…Limiting lactic acid production/accumulation would help to reduce or prevent the extent of acidosis in the rumen. A positive effect on lactic acid concentration as well as rumen pH was also observed under in vivo conditions (Mohammed et al ). Pinloche et al () observed a decrease in the concentration of d ‐ and l ‐lactate by 58% when diet of cattle was supplemented with 5 g day −1 of yeast.…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 78%
“…The decrease observed in pH values was due to accumulation of acids that occurs in a closed fermentation system, similar to that observed by Santos et al (). Despite the pH reduction, the pH value remained within the range indicated for the appropriate development of fibrolytic bacteria in the rumen (Mohammed et al ). An optimal NDF‐D is important for ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…The use benefit of yeasts as probiotics can be obtained by different forms of action. The alive and active yeasts in the rumen can compete with Streptococcus bovis by limiting lactate production (Mohammed et al ) or using excess lactate (Sirisan et al ) to reduce ruminal acidosis. The regulation of rumen pH can stimulate the activity of Selenomonas ruminantum and Megasphaera elsdenii , which consume lactic acid (Mohammed et al ) or use excess lactate (Sirisan et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation